2021
DOI: 10.1002/ajh.26112
|View full text |Cite
|
Sign up to set email alerts
|

Acute myeloid leukemia after age 70 years: A retrospective comparison of survival following treatment with intensive versus HMA ± venetoclax chemotherapy

Abstract: Effects of anemia and iron deficiency on quality of life in women with heavy menstrual bleeding. Acta Obstet Gynecol Scand. 2014;93: 654-660. 4. https://www.nimh.nih.gov/health/statistics/index.shtml. Accessed December 02, 2020. 5. Duke JM, Sibbritt DW, Young AF. Is there an association between the use of oral contraception and depressive symptoms in young Australian women? Contraception. 2007;75:27-31. 6. Mosher WD, Chandra A, Jones J. Sexual behavior and selected health measures: men and women 15-44 years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
(20 reference statements)
1
5
0
3
Order By: Relevance
“…Among patients who received HMA in the frontline, they observed CR/CRi rates of 32% and a 3‐year OS of 10%. Conversely, among patients who received intensive chemotherapy, they observed CR/CRi rates of 62% and 3‐year OS of 23%, concluding that intensive chemotherapy may be superior in achieving long‐term survival 45 . However, responses rates and long‐term OS in our study using DNT compare favorably with these data and may provide similar benefit with less incidence of toxicity in this older population.…”
Section: Discussionsupporting
confidence: 40%
“…Among patients who received HMA in the frontline, they observed CR/CRi rates of 32% and a 3‐year OS of 10%. Conversely, among patients who received intensive chemotherapy, they observed CR/CRi rates of 62% and 3‐year OS of 23%, concluding that intensive chemotherapy may be superior in achieving long‐term survival 45 . However, responses rates and long‐term OS in our study using DNT compare favorably with these data and may provide similar benefit with less incidence of toxicity in this older population.…”
Section: Discussionsupporting
confidence: 40%
“…Indeed, although the trial of DiNardo et al reported a median overall survival of 14.7 months (95% CI 11.9-18.7), real-world studies showed substantially lower survival. With the only exception of Cherry et al and Mirgh et al, which reported a median survival of more than 15 months, the other authors showed an overall survival ranging between 4 and 13 months [21,24,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. As a consequence, the pooled median survival in our meta-analysis was 9.37 months (95% CI 8.81-10.5), significantly lower than that reported by DiNardo et al This difference was also confirmed in the secondary analyses that we performed, in particular after we excluded studies enrolling subjects with worse prognoses (i.e., secondary, therapy-related, and TP53mutated AML).…”
Section: Discussionmentioning
confidence: 98%
“…The above‐outlined observations suggested the apparently crucial role of AHSCT in securing long‐term survival in MPN‐BP as well as the favorable short‐term survival impact of chemotherapy‐induced CR/CRi. Our recently published experience in AML patients above age 70 years was similar in confirming the survival advantage for intensive chemotherapy, for otherwise fit patients, and the value of HMA‐based therapy for prolonging short‐term survival in patients not considered fit to receive AML‐like induction chemotherapy 3 . The majority of patients with MPN‐BP are older than age 65 years and often suffer from comorbidities that make them ineligible for intensive chemotherapy 2 .…”
Section: Introductionmentioning
confidence: 73%